EARLY INITIATION OF BETA BLOCKERS FOLLOWING PRIMARY ENDOSCOPIC THERAPY FOR BLEEDING ESOPHAGEAL VARICES IN CIRRHOTICS - Salim, Adnan; Malik, Kashif; Farooq, Muhammad Omer; Butt, Umair; Butt, Arshad Kamal; Alam, Altaf (Journal of Ayub Medical College Abbottabad, 2017)
Background and Aims: Beta-blockers provide secondary prophylaxis following endoscopic therapy for variceal bleeding. Guidelines recommend starting beta-blockers 6 days after endoscopy to prevent masking hemodynamic signs of rebleeding. We aimed to see safety of earlier initiation of beta-blockers. Methods: Cirrhotic patients with upper GI bleed were given I.V vasoactive agents until undergoing endoscopy. Patients with only esophageal varices as source of bleed were recruited. Vasoactive agents were discontinued following variceal banding. The patients were observed for 12-18 hours, discharged on oral carvedilol 6.25mg BID and monitored for 6 weeks for rebleeding and mortality. Results: 50 patients were included, 27 (54%) male and 23 (46%) female. Average age was 43+3 years. Etiology of cirrhosis was HCV in 42 (84%), HBV in 6 (12%), HCV & HBV in 2 (4%) and indeterminate’¨in 1 (2%) patient. 17 (34%) patients had Child A, 22 (44%) Child B and 11 (22%) had Child C disease. Hospital stay was under 24 hours in 24 (48%), 24-48 hours in 15 (30%) and 48-72 hours in 11 (22%) patients. 5 (10%) patients underwent EGD within 6 hours of admission, 28 (56%) within 12 hours, 14 (28%) within 24 hours and 3 (6%) within 36 hours. No rebleeding, mortality or drug related adverse effects were noted during 6 weeks after discharge. Conclusions:Our study proves possibility of shorter management of variceal bleeding by having a 12-18 hour monitoring after endoscopic banding, followed by beta-blocker initiation and discharge. This will safely reduce physical and financial burden on health services. Background: Beta-blockers provide secondary prophylaxis following endoscopic therapy for variceal bleeding. Guidelines recommend starting beta-blockers 6 days after endoscopy to prevent masking hemodynamic signs of re-bleeding. We aimed to see safety of earlier initiation of beta-blockers. Methods: Cirrhotic patients with upper GI bleed were given intravenous vasoactive agents until undergoing endoscopy. Patients with only oesophageal varices as source of bleed were recruited. Vasoactive agents were discontinued following variceal banding. The patients were observed for 12-18 hours, discharged on oral carvedilol 6.25 mg BID and monitored for 6 weeks for re-bleeding and mortality. Results: Fifty patients were included, 27 (54%) male and 23 (46%) female. Average age was 43±3 years. Aetiology of cirrhosis was HCV in 42 (84%), HBV in 6 (12%), HCV & HBV in 2 (4%) and indeterminate’¨in 1 (2%) patient. Seventeen (34%) patients had Child A, 22 (44%) Child B and 11 (22%) had Child C disease. Hospital stay was under 24 hours in 24 (48%), 24-48 hours in 15 (30%) and 48-72 hours in 11 (22%) patients. Five (10%) patients underwent EGD within 6 hours of admission, 28 (56%) within 12 hours, 14 (28%) within 24 hours and 3 (6%) within 36 hours. No re-bleeding, mortality or drug related adverse effects were noted during 6 weeks after discharge. Conclusions: Our study proves possibility of shorter management of variceal bleeding by having a 12-18 hour monitoring after endoscopic banding, followed by beta-blocker initiation and discharge. This will safely reduce physical and financial burden on health services. Keywords: liver cirrhosis; Portal hypertension; variceal bleeding; beta-blockers